An Analysis of Social Media Accounts as Digital Heritage Within The Indonesian Legal System - Wayan Arieka Naka Maheswari; I Wayan Wesna Astara; I Nyoman Sukandia (International Journal Labs, 2026)
Advances in information technology have given rise to social media platforms such as TikTok and YouTube, which function not only as means of communication but also as sources of economic income in the form of digital assets. This study addresses two research questions: the legal status of social media accounts as objects of inheritance and the regulations governing the transfer of assets within social media accounts during the inheritance process. The objective of this study is to analyze the legal status of social media accounts as digital inheritance and to formulate regulations that provide legal certainty for heirs. This study offers theoretical benefits for the development of inheritance law and practical benefits for the government, notaries, the public, and heirs. The research method employed is normative legal research using legislative, conceptual, comparative, and factual legal approaches. Based on the research findings, social media accounts can be classified as objects of inheritance under civil law, Islamic law, and customary law because they constitute intangible property, possess economic value, involve copyright, and provide social benefits. However, the transfer of digital assets still faces obstacles related to the Terms of Service of the platforms, and there are currently no specific legal norms governing this matter, thereby creating legal uncertainty for heirs. Therefore, specific regulations regarding digital inheritance in Indonesia are necessary to provide legal certainty and legal protection for heirs.